Financial Analysis of Information Technology Investments: “Assessing Benefits through Cost-Benefit Analysis and Ranti’s Generic IS/IT Business Value Approach" - Estiyanti, Ni Made; Wiranti, Ni Made; Dewi, Eka Grana Aristyana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Technology drives economic growth and increases industrial competitiveness and has long been recognized for its dominance of industrial productivity. PT XYZ is a company engaged in the transportation services sector in Indonesia; from 2012 to 2017, PT XYZ carried out a massive digital transformation process by investing in information technology to improve its quality. This investment includes ERP, SAP implementation and improvement, RTS implementation and improvement, web-based information technology platforms, and mobile applications. This study aims to analyze the benefits of information technology investment made in PT XYZ using secondary data from the Company’s annual financial statements accessed through the Company’s website. The results of this study were conducted by analyzing financial statements from 2012 to 2020 using the Cost Benefit Analysis method and Ranti’s Generic IS / IT Business Value method. Based on the Analysis, investment in information technology benefits the Company without distinguishing between tangible and intangible benefits identified in the form of 8 sub-categories in 5 categories based on Ranti’s Generic IS/IT Business Value.